Experimentation of Tieu Equation by Energy Transfer Quantum Mechanics Cellular Function - Huu S. Tieu; Martin F. Loeffler (Fundamental Research and Application of Physical Science Vol. 4, 2023)
The foundation for any theory in Physics is Quantum Mechanics. This gives a description for the properties in the physical form of nature. Quantum Sciences studies particles on the atomic scale which involves subatomic particles. This is the fundamental basis for Quantum physics and the Quantum Sciences. Quantum Sciences includes Quantum Chemistry, Quantum Biology, and Quantum Field Theory. All of this total encompassing discipline studies the particle function and how it relates to the natural environment. Particles can be affected by themselves, other particles around them and even move and react in similar function. Tieu’s equation was developed to advance research for innovation and later to provide a convergence of information for the success of the substance in biological organisms’ giving explanation to processes like photosynthesis. Even though a toxic substance was introduced as described in the paper’s introduction to harm animal subjects and cause weight loss through toxicity, all of the animals in the study consistently gained weight on the first day of the experiment. Animal studies suggests that in a toxic environment that the biological mechanism becomes more efficient and requires less input to function properly, yet the efficiency is improved to the point that the mechanism can even store unused energy for a future need by the mechanism. Blood test results can be used to create tests. Human patients’ health was also observed to improve as the substance was administered to the biological mechanism, and plants were initially exposed to the substance to observe results. This is consistent with the Tieu equation which provides that wave function is created as the introduction of the substance to the biological mechanism which supports Quantum Mechanics. The Tieu equation shows how a particle can be moved by temperature, for instance, producing energy that can cross the blood-brain barrier. In order to include the substance administered through laboratory standards using Good Laboratory Practises in accordance with Title 40 C.F.R. 158, the Tiu equation’s methods incorporate animal studies. Human patients were administered the substance by medical professionals who are experts in their field and are familiar with patient responses. Plant applications were obtained for the purpose of observing and guiding ongoing experiments of animals representing the biologics mechanism. An impressive line that has followed the Tiu equation to constantly show progress in the introduction of the Innovation to biologic systems has been demonstrated by animal research along with patient blood test results. The mechanism reacts to the material by producing energy that has an effective response in the mechanism. Plant organisms responded to observations of them and were observed to be improving through visual observation.